2023
DOI: 10.1186/s12885-023-10846-x
|View full text |Cite
|
Sign up to set email alerts
|

99mTc-MAA accumulation within tumor in preoperative lung perfusion SPECT/CT associated with occult lymph node metastasis in patients with clinically N0 non-small cell lung cancer

Abstract: Background 99mTc-MAA accumulation within the tumor representing pulmonary arterial perfusion, which is variable and may have a clinical significance. We evaluated the prognostic significance of 99mTc-MAA distribution within the tumor in non-small cell lung cancer (NSCLC) patients in terms of detecting occult nodal metastasis and lymphovascular invasion, as well as predicting the recurrence-free survival (RFS). Methods Two hundred thirty-nine NSCLC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…OLNM is a potential risk factor for recurrence and metastasis, being of great clinical significance for prognosis ( 19 , 20 ). In comparison to a large cohort of 2,623 NSCLC patients who underwent surgery, wherein 29.7% had LNM ( 21 ), our study revealed a similar rate (28.4%) of LNM in ALK-rearranged NSCLC patients, with 51.5% of which being occult.…”
Section: Discussionmentioning
confidence: 99%
“…OLNM is a potential risk factor for recurrence and metastasis, being of great clinical significance for prognosis ( 19 , 20 ). In comparison to a large cohort of 2,623 NSCLC patients who underwent surgery, wherein 29.7% had LNM ( 21 ), our study revealed a similar rate (28.4%) of LNM in ALK-rearranged NSCLC patients, with 51.5% of which being occult.…”
Section: Discussionmentioning
confidence: 99%